Guided Imagery to Improve Mental Health in Cancer Patients with Chemotherapy: Literature Review - Nirmala Amir; Ariyanti Saleh; Syahrul Said (STIKep PPNI Jawa Barat, 2022)
Aims: The purpose of this study was to review the research literature related to the use of Guided imagery on the mental health of cancer patients undergoing chemotherapy. Methods: The design of this review is a literature review. Five quantitative experimental articles and RCTs were obtained from the database: PubMed, Proquest, Clinicalkey nursing, Science Direct, with the criteria of experimental articles providing guided imagery interventions for chemotherapy patients, published 2011-2021, in English and Indonesian. Results: The findings of this review article were guided imagery intervention, two articles combined PMR relaxation, and three articles carried out guided imagery with deep breath relaxation. The duration of guided imagery differed in some studies from 15 minutes to 30 minutes with various sessions either supervised or conducted independently with compact disc (CD) recordings. The results of the findings that guided imagery can reduce mental health problems such as stress, anxiety and depression experienced by cancer patients undergoing chemotherapy. Conclusion: Guided imagery is a practical, easy, and simple action that can be taken to reduce mental health problems in cancer patients with chemotherapy.